Badan Usaha Milik Desa (Bumdesa) dalam Perspektif Desentraslisasi Pembangunan - Afero, Deni; Rosalia, Feni; Budiono, Pitojo (Jurnal Studi Pemerintahan dan Akuntabilitas, 2022)
Purpose: this study is to find out the activities carried out by Village Owned Enterprises (BUMDes) and the amount of capital participation that has been channeled for economic turnover that can generate Village Original Income which can be useful in supporting development in the region. Improving people's welfare is an important government agenda. , both in formulating long-term plans and in determining political policies, this condition is often a challenge for the government in determining targeted programs for equitable development of the people. The government in 2014 issued Law Number 6 concerning Villages which is a form of central government to implement development that is decentralized to rural areas. Research methodology: this study is a qualitative research method using data collection techniques used by using observation and interview methods and observations made to BUMDes units that are considered successful in their management, then data analysis is carried out using data reduction techniques which are then presented for withdrawal. Results: The South Lampung Regency Government makes the BUMDes program a good opportunity to open new business opportunities at the rural level using existing capital. The South Lampung Regency Government at least recorded a BUMDes capital participation until 2020 of Rp. 57,158,850,296,- and it was recorded that in 2020 it could contribute to PADes (Village Original Income) of Rp. 1,419,775,526,-. A total of 256 BUMDes within the South Lampung Regency Government have played an active role in opening new business opportunities that can be competitive in improving welfare and alleviating poverty in South Lampung Regency. Contribution: In its budgeting, the Government has emphasized the mechanism for capital participation programmed by the village to accommodate the needs of BUMDes in its working area. Empowerment-based programs and activities are actually mostly carried out by the government, but this time the author tries to increase the role of BUMDes in an effort to improve community welfare.